Changing trends of tobacco use in a teenage population in western Pennsylvania. - Guggenheimer, J (1986)
Information on tobacco use was obtained from an anonymous questionnaire distributed to 609 8th, 9th, and 10th grade students in the Pittsburgh area. The data disclosed that 22 per cent of the girls and 11 per cent of the boys were smoking. However, 35 per cent of the young men reported using smokeless tobacco; snuff dipping (6 per cent), tobacco chewing (10 per cent), and snuff and/or tobacco chewing (19 per cent).